Indikator "Bertentangan Dengan Kepentingan Umum" Sebagai Dasar Pembatalan Peraturan Daerah - Victor Juzuf Sedubun (SASI, 2012)
Formation regulation must meet the indicator does not contradict the legislation ofhigher and not contrary to public interest. If both indicators are not met in the establishmentof a law, then in the evaluation by the Government, there apabil established law contrary tothe legislation of higher and contrary to public interest, the Government may cancel a legalproduct. Indicators of general interest in the cancellation law is vague norm, because thisindicator is to open a space for the Government to make the interpretation of the meaning ofpublic interest norms. Very complex public interest, public interest is not always to beunderstood as a national interest, regional interest may also be the public interest because itincludes all interests in the communal areas. Interest means the area of interest to allindividuals in the region as a whole.